Glutathione and Homoglutathione Synthetases of Legume Nodules. Cloning, Expression, and Subcellular Localization - Moran, Jose F. (American Society of Plant Physiologists, 2000)
The thiol tripeptides glutathione (GSH) and homoglutathione (hGSH) are very abundant in legume root nodules and their synthesis is catalyzed by the enzymes γ-glutamylcysteine synthetase (γECS), GSH synthetase (GSHS), and hGSH synthetase (hGSHS). As an essential step to elucidate the role of thiols in N(2) fixation we have isolated cDNAs encoding the three enzymes and have quantified the transcripts in nodules. Assay of enzyme activities in highly purified nodule organelles revealed that γECS is localized in the plastids, hGSHS in the cytosol, and GSHS in the cytosol and mitochondria. These results are consistent with sequence analyses. Subcellular fractionation of nodules also showed that bacteroids contain high thiol concentrations and high specific γECS and GSHS activities. Results emphasize the role of nodule plastids in antioxidant protection and in control of thiol synthesis, and suggest that plastids may be important in the stress response of nodules. Overall, our results provide further evidence that thiol synthesis is critical for nodule functioning.